(untitled) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2026)
Urban development in many metropolitan regions is shifting from monocentric to polycentric structures, offering pathways toward more sustainable, equitable, and resilient cities. This study analyses the polycentric transformation of Bandung’s Central Business District (CBD) using an integrated spatial and econometric approach. Data from 118 observation points across seven commercial corridors were examined through Local Indicators of Spatial Association (LISA) and bootstrapped regression with 10,000 resamples to improve reliability. The results reveal a significant spatial clustering pattern (Moran’s I = 0.482, p < 0.05) and identify four functional clusters: Primary Commercial Nucleus, Strategic Corridor, Sub-Centre Embryo, and Low-Intensity Zone. Regression analysis demonstrates strong explanatory power (R² = 0.821), with cultural and locational factors exerting the most decisive influence, followed by economic activity and accessibility. In contrast, government policy shows a negative association, suggesting that regulatory complexity can constrain growth and spatial agglomeration. These findings indicate that Bandung’s polycentric evolution is shaped more by cultural vitality and market dynamics than by top-down policy intervention. The study contributes empirical evidence to debates on urban polycentricity and provides practical insights for property valuation, spatial planning, and taxation frameworks. By linking the results to the United Nations Sustainable Development Goal 11, the research highlights polycentric development as a viable strategy for promoting inclusive and sustainable metropolitan futures.